2000
DOI: 10.2307/2656690
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed traits of Lobelia inflata (Campanulaceae): sources and fitness consequences

Abstract: Seed germination constitutes an important event in the life cycle of plants. Two related seed traits affect fitness: seed size and the timing of seed germination. In three sets of experiments, we (1) partition the sources of seed-size variance in Lobelia inflata into components attributable to fruit size, relative fruit position, and parental identity; (2) examine the influence of pregermination conditions and seed size on time to germination; and (3) assess the fitness consequences of seed size and germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 46 publications
3
131
1
3
Order By: Relevance
“…Regrettably, we found no published information on the relationship between embryo size and fitness or yield in maize. Seed size is a critical determinant of fitness in many species, affecting germination probability, seedling performance, and survival (46)(47)(48)(49). However, the contribution of embryo size to fitness in these studies is unclear, although many of these reports involved taxa with exalbuminous seeds, for which the embryo is the major component.…”
Section: Coefficient Of Relatedness Affects Embryo But Not Endospermmentioning
confidence: 98%
“…Regrettably, we found no published information on the relationship between embryo size and fitness or yield in maize. Seed size is a critical determinant of fitness in many species, affecting germination probability, seedling performance, and survival (46)(47)(48)(49). However, the contribution of embryo size to fitness in these studies is unclear, although many of these reports involved taxa with exalbuminous seeds, for which the embryo is the major component.…”
Section: Coefficient Of Relatedness Affects Embryo But Not Endospermmentioning
confidence: 98%
“…Therefore, not only does germination timing influence the survival of young seedlings (Biere 1991;Gross and Smith 1991;Simons and Johnston 2000;Donohue et al 2005b), but it has persistent effects on adult life stages as well. The season of germination has been known to alter basic life-history expression in other systems, determining whether plants will be annuals as opposed to biennials (Kalisz 1989;Kalisz and Wardle 1994;Galloway 2001Galloway , 2002 or summer annuals as opposed to winter annuals (Ratcliffe 1976;Effmertova 1967;Evans and Ratcliffe 1972;Nordborg and Bergelson 1999).…”
Section: Plasticity Of Life History In Response To Germinationmentioning
confidence: 99%
“…A number of studies have demonstrated that seed mass is a major determinant of seed reserves, and substantial seed mass variation exists at many scales (i.e. among populations and plants and within plants) in a range of terrestrial species (Ågren 1989, Matthies 1990, Mehlman 1993, Obeso 1993, Lord 1994, McKee & Richards 1996, Navarro 1996, Krannitz 1997, Vaughton & Ramsey 1998, Simons & Johnston 2000 because of reduced resource availability throughout the growing season, or architectural or physiological constraints operating during seed provisioning (Susko & Lovett-Doust 2000, Vaughton & Ramsey 2001. Differences in seed mass may affect seedling recruitment via effects on seedling growth and survivorship.…”
Section: Introductionmentioning
confidence: 99%